PRODUCT STRATEGY, BRAND EQUITY, AND SERVICE QUALITY EFFECTS ON PURCHASE INTENTION AMONG LINOW LAKE TOURISTS - Silvya Lefina Mandey; Victor Paskah Kalawat Lengkong; Jenny Emma Agustin Kandou (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines a model of how product strategy, brand equity, and service quality influence purchase intention among tourists visiting Linow Lake, Tomohon City, North Sulawesi, Indonesia. Using a causal associative design, data were collected online via a structured questionnaire (Google Form) from 100 respondents selected through purposive non-probability sampling. Product strategy was measured through product variety, quality, design, features, packaging, size, and return; brand equity through brand awareness, perceived quality, brand association, and brand loyalty; and service quality through reliability, responsiveness, assurance, empathy, and tangibles. Purchase intention was assessed through indicators related to planned purchase/visit intention, patience/willingness, and information search. All measurement items were valid (r-count > r-table) and reliable (Cronbach’s alpha > 0.6). Classical assumption tests indicated normal residual distribution, no multicollinearity (VIF < 10; tolerance > 0.10), and no heteroscedasticity. Multiple linear regression results show that product strategy and brand equity have positive and significant effects on purchase intention, while service quality is not statistically significant in the regression model. Simultaneously, the three predictors significantly explain purchase intention. The findings highlight the importance of strengthening tourism product attributes and brand equity to enhance tourists’ purchase intention toward Linow Lake as a destination.